Non-invasive detection of human cardiomyocyte death using methylation patterns of circulating DNA - Hai Zemmour (Nature Portfolio, 2018)
The detection of cardiomyocyte death is a critical aspect in the diagnosis and monitoring of heart diseases. Here the authors show that cardiomyocyte-specific methylation patterns of circulating cell-free DNA may serve as a biomarker of cardiac cell death in infarcted and septic patients.